Nanocrystalline spinel zinc-substituted cobalt ferrite thick film an efficient ethanol sensor. (December 2021) - Powar, R.R.; Parale, V.G.; Phadtare, V.D.; Wategaonkar, S.B.; Mane, R.K.; Gunjkar, J.L.; Patil, D.R.; Piste, P.B.; Park, H.-H.; Zambare, D.N.
Abstract: This study considered Zn-substituted cobalt ferrite (Zn x Co1- x Fe2 O4 ( x = 0.0–1.0) (ZCF)) thick films structural, morphological, and electrical properties; and gas sensing performance. The ZCF thick film sensor was screen printed on a glass substrate and tested for different analyte gases, including H2, H2 S, CO2, Cl2, NH3, LPG, and C2 H5 OH. We used X-ray photoelectron spectrometry to investigate composition, chemical state, iron/cobalt or zinc ratio, and cation distribution within Zn-substituted cobalt spinel ferrite tetrahedral and octahedral sites without impurities. FESEM and HR-TEM confirmed grain dimensions between 0.13 and 0.23 μm and porous, nearly spherical to flake-like morphology for the ZCF samples. Sample DC resistivity reduced with increasing temperature, confirming semiconductor nature. Thick film ZCF composition achieved highest the gas response and selectivity to 100 ppm ethanol at room temperature (30 °C). Overall results confirmed that flake-like ZCF sensors could be effective ethanol gas sensors. Highlights: An easy and fast synthesis of Zn-substituted CoFe2 O4 nanoparticles via surfactant-assisted chemical co-precipitation method. The Zn-substituted CoFe2 O4 thick film exhibits semiconducting nature. A Zn-substituted CoFe2 O4 thick film showed flake-like morphology for efficient ethanol sensor. The Zn0.25 Co0.75 Fe2 O4 sensor exhibited excellent long term stability, highest response, and selectivity.